Genetic and immunologic features associated with thrombocytopenia progression and poor prognosis in patients with myelofibrosis - Kim, Tong Yoon; Eom, Ki-Seong; Lee, Ji Yoon; Lee, Jong-Mi; Kim, Myungshin; Lee, Sung-Eun (Frontiers in Medicine, 2024)
Myelofibrosis, which includes primary myelofibrosis (PMF) and secondary myelofibrosis (SMF), can exhibit cytopenic features associated with poor outcomes; however, the underlying mechanisms are unclear. Moreover, characterized by its aggressive nature and limited therapeutic options, myelofibrosis poses a major clinical challenge in hematology. Therefore, in this study, we aimed to identify genetic and immunologic features associated with thrombocytopenia progression and poor prognosis. Methods: The study involved 226 patients with PMF or SMF, who were categorized into three groups: platelet count ≥ 100 × 10 9 /L (PLT≥100 group; n = 131), progression to thrombocytopenia (PROG group; n = 64), and platelet count < 100 × 10 9 /L (PLT<100 group; n = 31). Results: Survival analysis revealed 4-year overall survival rate of 57.7%, 89.4%, and 93.9% for the PLT<100, PROG, and PLT≥100 groups, respectively. Time-dependent covariate analysis of the PLT≥100 and PROG groups revealed inferior overall survival rate of the PROG group. mutations were associated with poor overall survival. Flow cytometry revealed fewer CD45RA + CD4 + T cells in the PROG group than in the PLT>100 group. ASXL1 mutations were more prevalent in the PROG group than in the other groups, correlating with a reduced number of CD45RA + CD4 + T cells. Discussion: ASXL1 mutation and low CD45RA + CD4 + Tcell counts correlated with progression to thrombocytopenia. Our findings underscore the clinical significance of thrombocytopenia dynamics in MF progression and prognosis, with implications for patient management and therapeutic interventions.